Gene-Based Therapeutics for Parkinson’s Disease - Karim E. Shalaby (12267224) (2022)
Parkinson’s disease (PD) is a complex multifactorial disorder that is not yet fully surmised, and it is only when such a disease is tackled on multiple levels simultaneously that we should expect to see fruitful results. Gene therapy is a modern medical practice that theoretically and, so far, practically, has demonstrated its capability in joining the battle against PD and other complex disorders on most if not all fronts. This review discusses how gene therapy can efficiently replace current forms of therapy such as drugs, personalized medicine or invasive surgery. Furthermore, we discuss the importance of enhancing delivery techniques to increase the level of transduction and control of gene expression or tissue specificity. Importantly, the results of current trials establish the safety, efficacy and applicability of gene therapy for PD. Gene therapy’s variety of potential in interfering with PD’s pathology by improving basal ganglial circuitry, enhancing dopamine synthesis, delivering neuroprotection or preventing neurodegeneration may one day achieve symptomatic benefit, disease modification and eradication. Other Information Published in: Biomedicines License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.3390/biomedicines10081790